A diet-wide Mendelian randomization analysis: causal effects of dietary habits on type 2 diabetes - Xiao, Rui; Dong, Li; Xie, Bo; Liu, Beizhong (Frontiers in Nutrition, 2024)
Background Traditional clinical studies have indicated a link between certain food intakes and type 2 diabetes (T2D), but the causal relationships between different dietary habits and T2D remain unknown. Using Mendelian randomization (MR) approaches, we investigated the potential causal association between dietary habits and T2D risk. Methods We collected publicly available genome-wide association studies’ summary statistics for 18 dietary habits from the UK Biobank and T2D data from the DIAbetes Genetics Replication And Meta-analysis (DIAGRAM) consortium. We applied the inverse variance weighted (IVW) method, supplemented with the MR-Egger method, weighted median method (WMM), simple method, weighted mode, MR-Egger regression, and the MR pleiotropy residual sum and outlier test to determine whether a particular diet was causal for T2D. Results Reliable and robust MR estimates demonstrated that poultry intake has a causal effect on a higher risk of T2D (IVW: OR 6.30, 95% CI 3.573–11.11, p = 2.02e − 10; WMM: OR 5.479, 95% CI 0.2758–10.88, p = 1.19e − 06). Conversely, dried fruit intake (IVW: OR 0.380, 95% CI 0.237–0.608, p = 5.57e − 05; WMM: OR 0.450, 95% CI 0.321–0.630, p = 3.33e − 06) and cereal intake (IVW: OR 0.455, 95% CI 0.317–0.653, p = 1.924e − 05; WMM: OR 0.513, 95% CI 0.379–0.694, p = 1.514e − 05) were causally associated with T2D as protective factors. Sensitivity analyses confirmed the reliability and robustness of these findings. Discussion Our study established the causal effects of poultry intake, dried fruit intake, and cereal intake on T2D, identifying poultry intake as a risk factor and the other two as protective factors. Further research into potential mechanisms is required to validate these novel findings.